Awareness of natural breastfeeding milk among mothers and the importance of colostrum within the first hour of birth in India - Akinola, Ajoke; Karama, Rahama Sanusi; Rajput, Manju (International Journal Of Community Medicine And Public Health, 2022)
Children should not suffer from the lack of adequate knowledge or ignorance from their parents. Breastfeeding colostrum is extremely useful for the immunity and growth of the newborn, as it is having been documented to improve neonatal survival, and protective against the infection specific mortality among newborn and mothers. The secondary data presented in this paper was abstracted from well-known search engines performed in March 2022. Search engines like Pubmed and Google scholar. In Pubmed 8 articles were returned and Google scholar 11 articles/ key words related to breastfeeding and colostrum and first hour of birth in India. Includes 19 studies altogether, all papers were done within 2019 to 2022 and published in English. Study result showed several preventive diseases among the children and their mother. Spreading awareness about natural breastfeeding and the importance of colostrum among mothers is the key to successfully contribute towards reduction of child mortality. May be carried forward for public health intervention of further research to better informed information, education and counselling for pregnant women for sustainable future of our children according to the United Nations sustainable goals, no one should be left behind.